Analisis Yuridis Kekerasan dalam Rumah tangga yang dilakukan Istri terhadap Suami - Muhammad Raflih (Jurnal Hukum Lex Generalis, 2025)
Domestic violence can also be experienced by husbands as victims, although it has received little social attention. This study aims to examine the forms of violence perpetrated by wives and their criminal accountability from a legal political perspective. The method used is normative legal research. The results show that Law Number 23 of 2004 is essentially gender-neutral, but in its implementation tends to place more emphasis on protecting women, thus the position of male victims has not been fully accommodated. Wives as perpetrators can still be held criminally accountable if they fulfill the elements of a crime. Therefore, more inclusive law enforcement guidelines and increased outreach are needed to ensure victim protection without gender discrimination.